Max Weber in the tropics: How global climate politics facilitates the bureaucratization of forestry in Indonesia. Issue 1 (6th August 2019) - Lederer, Markus; Höhne, Chris
Abstract: Reducing Emissions from Deforestation and Forest Degradation (REDD+) is one of the most advanced global climate governance arrangements and we show that it contributes to the buildup of autonomous capacities and reliable procedures in areas of rather limited statehood. These partially unintended effects can be conceptualized as an increasing rational–legal bureaucratization, which has been initiated through both external and domestic actors as we illuminate in the case of Indonesia's forestry sector in the period from 2007 until 2017. Our finding is that a bureaucratization of a new kind is increasingly strengthened in Indonesia's forest despite enduring patterns of neopatrimonialism, emerging signs of new public management approaches, and the strengthening of functional equivalents such as community‐based forest management. We thus claim that Max Weber's perspective on the prospects and problems of rational–legal bureaucratization is still valuable, even when travelling to the tropics.